Natural Product Chemistry (NPC) Laboratory Activity in Indonesia - Hakim, Aliefman; Jufri, Abdul Wahab; Jamaluddin, Jamaluddin; Ramandha, Muhammad Eka Putra (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
The purpose of this research is to integrate to provide design recommendations for the implementation of good natural product chemistry (NPC) laboratory activity. This study was used systematic review which consists of data presentation, data reduction, and drawing conclusions. The data sources come from several articles. The data are: (1) data on natural product chemistry (NPC) laboratory activity methods, (2) data on the validity of the natural product chemistry (NPC) laboratory activity module, (3) data on the effectiveness of the natural product chemistry (NPC) laboratory activity module method data. Module validity was analyzed using the aiken index. The results of the analysis show that the implementation of the natural materials practicum will be carried out if it meets several requirements, namely (1) practicum design (2) practicum module. The validity results show that the natural materials chemistry practicum module is very feasible and practical to use.